QT Prolongation and T‐Wave Alternans during Catheter Ablation of Atrial Fibrillation: A Case Report - Saini, Aditya (Ann Noninvasive Electrocardiol, 2013)
We report a case of a 63‐year‐old woman who developed profound QT prolongation, T‐wave alternans, and spontaneous ventricular fibrillation during catheter ablation of atrial fibrillation. A thorough search into the possible mechanisms identified the use of sevoflurane, an inhalational gas anesthetic as the culprit. The patient was converted to propofol anesthesia and her QT interval normalized promptly.